2018
DOI: 10.1159/000486457
|View full text |Cite
|
Sign up to set email alerts
|

Stent Reconstruction of Carotid Tonsillar Loop Dissection Using Telescoping Peripheral Stents

Abstract: Background: Endovascular treatment options for internal carotid artery (ICA) dissection with tandem intracranial occlusion are evolving. We report 2 cases of stent reconstruction of carotid loop dissections. Methods: Two patients with symptomatic ICA dissections of true 360° tonsillar loops and tandem intracranial occlusions were treated with manual aspiration thrombectomy (MAT) and telescoping Zilver self-expanding peripheral stents. Patient demographics, clinical presentations, endovascular techniques, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…6,7 However, because their low pore density and radial force may cause thrombus migration from the pseudolumen into the stents and insufficient opening of the stenoocclusive segment, these devices may not be appropriate for carotid dissection. In contrast, Zussman et al 8 demonstrated the efficiency of telescoping-stent reconstruction of the carotid tonsillar loop dissection using Zilver self-expanding peripheral stents. However, in one of the present cases (case 1), this stent delivery system could not progress through the looped segment, whereas the PED delivery system was easily navigated through the lesion.…”
Section: Discussion Observationsmentioning
confidence: 95%
“…6,7 However, because their low pore density and radial force may cause thrombus migration from the pseudolumen into the stents and insufficient opening of the stenoocclusive segment, these devices may not be appropriate for carotid dissection. In contrast, Zussman et al 8 demonstrated the efficiency of telescoping-stent reconstruction of the carotid tonsillar loop dissection using Zilver self-expanding peripheral stents. However, in one of the present cases (case 1), this stent delivery system could not progress through the looped segment, whereas the PED delivery system was easily navigated through the lesion.…”
Section: Discussion Observationsmentioning
confidence: 95%